2017
DOI: 10.3390/molecules22101627
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption of Triterpenoids and Flavonoids from Glycyrrhizae radix et rhizoma in the Human Caco-2 Monolayer Cell Model

Abstract: Glycyrrhizae radix et rhizoma has been used as a traditional Chinese medicine for the treatment of various diseases. Triterpenoids and flavonoids from the plant have many beneficial effects and their chemical structures are modified in the gastrointestinal tract after oral administration. However, absorption of these triterpenoids and flavonoids still needs to be defined. Here, the uptake and transepithelial transport of the selected major triterpenoids, glycyrrhizin (1), glycyrrhetic acid-3-O-mono-β-d-glucuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
6
26
0
Order By: Relevance
“…LZD is mostly used for the relief of nausea or vomiting, stomachache, diarrhea or watery stools, and rugitus. Modern studies have demonstrated that extracts or compounds from CR [7][8][9] or GRR [10][11][12][13] possess multiple physiological effects, such as anti-inflammation, antioxidation, gastrointestinal function regulation, and immune function regulation. We have shown that AMR stimulated gastrointestinal epithelial repair through polyamine-mediated Ca 2+ and K + signaling pathways [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…LZD is mostly used for the relief of nausea or vomiting, stomachache, diarrhea or watery stools, and rugitus. Modern studies have demonstrated that extracts or compounds from CR [7][8][9] or GRR [10][11][12][13] possess multiple physiological effects, such as anti-inflammation, antioxidation, gastrointestinal function regulation, and immune function regulation. We have shown that AMR stimulated gastrointestinal epithelial repair through polyamine-mediated Ca 2+ and K + signaling pathways [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Other reasons for low mass balance could be the retention of the compounds inside the cells or in the cell membranes, or their adhesion to plastic materials . Despite this limitation, suitability of the model and permeability method was demonstrated for the correct formation of the tight junctions of Caco‐2 cells (Figure ), and by the P app value for propranolol which was very similar to those reported by other authors . Thus, the information obtained from this model was enough to establish low permeability of rutin in all the test treatment but improved by the plant extract and fraction.…”
Section: Discussionsupporting
confidence: 78%
“…These findings indicate that LCD is low in toxicity. In addition, while common flavonoids generally have low bioavailability in humans, LCs have been shown to be well absorbed through passive diffusion through the Caco-2 cell monolayer, which is a human intestinal cell line [26]. Since intestinal permeability is an important factor influencing the bioavailability of drugs, LCs can be expected to have high bioavailability in the human body.…”
Section: Discussionmentioning
confidence: 99%